Associations of ANGPT2 expression and its variants (rs1868554 and rs7825407) with multiple myeloma risk and outcome - Popek-Marciniec, Sylwia; Styk, Wojciech; Chocholska, Sylwia; Szudy-Szczyrek, Aneta; Sidor, Katarzyna; Swiderska-Kolacz, Grazyna; Hus, Marek; Czerwik-Marcinkowska, Joanna; Zmorzynski, Szymon (Frontiers in Oncology, 2025)
The growth of blood vessels from the existing vasculature has a significant impact on the course of multiple myeloma (MM). The ANGPT2 (angiopoietin-2) protein is encoded by the ANGPT2 gene and plays an important role in angiogenesis. The expression of proangiogenic proteins is influenced not only by microenvironmental factors but also by genetic changes. We analyzed two variants/polymorphisms of the ANGPT2 gene, rs1868554 (T>A) and rs7825407 (G>C). Both are located in the intron sequence and can affect the final mRNA sequence by modifying splicing.PurposeTherefore, we assessed the impact of selected variants on ANGPT2 gene expression at the mRNA and protein levels. Additionally, we evaluated the associations of the analyzed genetic changes with the clinical and laboratory parameters of the disease and the response to bortezomib/thalidomide-based therapies. We hypothesize that variants and expression of the ANGPT2 gene may be associated with a greater risk of MM development and may also affect the response to treatment in MM patients.Patients and methodsGenomic DNA extracted from 103 newly diagnosed MM patients and 120 healthy blood donors was used to analyze ANGPT2 variants (via automated DNA sequencing). RNA was subjected to real-time PCR to determine ANGPT2 expression at the mRNA level. The concentration of angiopoietin-2 (in MM sera) was determined by ELISA.ResultsThe results of our study showed that individuals with the AA genotype of rs1868554 and the CC genotype of rs7825407 had a greater risk of developing MM (OR=6.12, p=0.02 and OR=6.01, p=0.02, respectively). The ANGPT2 gene variants did not affect ANGPT2 expression at the mRNA level. However, ANGPT2 expression was positively correlated with CRP (Spearman’s rho 0.26, p<0.05) and negatively correlated with LDH (Spearman’s rho -0.25, p<0.05) in MM patients.ConclusionOur results showed that ANGPT2 expression at the mRNA level correlates with CRP, a negative prognostic factor in MM. The ANGPT2 protein is a proangiogenic factor, and its concentration is significantly greater in MM patients than in healthy individuals, which was also confirmed in our research. Therefore, this protein with VEGF and HB-EGF, should be considered in the future as a markers of angiogenesis in MM.